The Effect of Patient Satisfaction on Patient Loyalty Mediated by Patient Trust and Hospital Brand Image at the Jakarta Education Dental and Oral Hospital - Tanya Aya Sofia (Journal of Social Research, 2023)
This study aims to find out and analyze "The Effect of Patient Satisfaction on Patient Loyalty mediated by Patient Trust and Hospital Brand Image at Jakarta Educational Dental and Oral Hospital". The data collection technique method uses non-probability sampling with a purposive sampling method. The data was collected directly from a sample that had adjusted the criteria and disseminated through a questionnaire to 250 respondents using a Likert scale of 1-5 where 1 showed strong disapproval, while 5 indicated strongly agreed. The statements in this study consisted of 25 statements obtained from four variables, namely patient satisfaction, patient loyalty, patient trust, and hospital brand image. The questionnaire is distributed through Google Forms. The analytical methods used in this study are Partial Least Square (PLS) and Structural Equation Model (SEM). The results of this study show that patient satisfaction has a positive influence on patient loyalty, patient satisfaction has a positive influence on patient trust, patient trust has a positive influence on patient loyalty, patient satisfaction has a positive influence on hospital brand image, Hospital Brand Image has a positive influence on patient loyalty, patient satisfaction has a positive influence on patient loyalty mediated by patient trust, patient satisfaction has a positive influence on patient loyalty mediated by Hospital Brand Image.